Correction: Catalytic conversion of biomass derivatives to lactic acid with increased selectivity in an aqueous tin(ii) chloride/choline chloride system. Issue 18 (30th August 2018) - Bayu, Asep; Yoshida, Akihiro; Karnjanakom, Surachai; Kusakabe, Katsuki; Hao, Xiaogang; Prakoso, Tirto; Abudula, Abuliti; Guan, Guoqing
Abstract : Correction for 'Catalytic conversion of biomass derivatives to lactic acid with increased selectivity in an aqueous tin(ii ) chloride/choline chloride system' by Asep Bayu et al., Green Chem., 2018, DOI: 10.1039/c8gc01022f.